Disruption in Manufacturing Industry - The Future of Global Workforce - Bambe, PhD, Dayo Ife (Advances in Social Sciences Research Journal, 2019)
The aim of this research was to evaluate the future of the global workforce aligned with the disruptive technologies in the manufacturing industry. The impacts of 5G, robotics, artificial intelligence, and machine learning were focused on current research. The purpose was to identify the possible safety net, which could be used by the governments and regulatory authorities to deal with the negative effects of technologies on the workers’ displacement in the next 5 to 10 years. Through the implementation of the inductive research methodology based on structured survey questionnaire administered with the sample of 100 employees working in the manufacturing sector, effects of disruptive technologies on the employment situation, production activity and overall organisation performance were addressed. Findings of the investigation have confirmed that new technologies have positive impacts on the production activity and overall organisational performance. New technologies are contributing vitally to increasing the production output, production quality, improving the cost of delays, increasing efficient waste management, reliable and consistent growth and enhanced profitability for the manufacturing companies. In contrary, these technologies are also having negative effects on the employment situation such as reduced recruitment, training, compensation, and increased unrest. Lastly, the set of recommendations directing towards introducing governmental regulations and policies for mandatory training, balanced compensation and increased hiring, are expected to have a significant positive contribution for tackling the issue of displacements.